1987
DOI: 10.1016/s0010-9452(87)80016-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcoding Sound to Spelling: Single or Multiple Sound Unit Correspondence?

Abstract: We report a detailed analysis of the written spelling of an aphasic patient, KT, in whom no viable comprehension could be demonstrated despite accurate repetition and fluent speech (transcortical sensory aphasia). His spelling conformed in all respects with the definition of an orthographic/lexical dysgraphic such that his writing of regular, orthographically unambiguous words and nonsense syllables was entirely satisfactory. Lexical variables such as word class or word frequency had no effect on his performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
4

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(25 citation statements)
references
References 13 publications
1
20
0
4
Order By: Relevance
“…Case studies of patients with a graphemic buffer disorder (Baxter & Warrington, 1987;Caramazza & Miceli, 1990;Zesiger & de Partz, 1997) indicate that the recall of orthographic information is indeed regulated by the syllable structure of words. It seems that the storage of orthographic information in the graphemic buffer-once lexical access has occurred for words and chunking has taken place for pseudowords-is achieved via a rehearsal process, which is sensitive to the processing load (measured in number of syllables).…”
Section: Discussionmentioning
confidence: 99%
“…Case studies of patients with a graphemic buffer disorder (Baxter & Warrington, 1987;Caramazza & Miceli, 1990;Zesiger & de Partz, 1997) indicate that the recall of orthographic information is indeed regulated by the syllable structure of words. It seems that the storage of orthographic information in the graphemic buffer-once lexical access has occurred for words and chunking has taken place for pseudowords-is achieved via a rehearsal process, which is sensitive to the processing load (measured in number of syllables).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the analyses of spelling errors exhibited by certain patients are consistent with the involvement of sublexical as well as lexical knowledge. In effect, some patients have been found to be able to produce nonwords while performing poorly on words, and more particularly, irregular words (e.g., Baxter & Warrington, 1987;Beauvois & Dérouesné, 1981;Behrmann & Bub, 1992;Goodman & Caramazza, 1986;Sanders & Caramazza, 1990), while the opposite observation has been reported in other patients (e.g., Baxter & Warrington, 1985;Bub & Kertesz, 1982;Shallice, 1981). This double dissociation has been taken as strong support for the existence of 59…”
mentioning
confidence: 89%
“…For example, Baxter and Warrington (1987) have suggested that only a single idiosyncratic mapping should be represented. In constrast, Goodman and Caramazza (1986) have proposed that multiple phoneme-tographeme mappings are represented for each phoneme, e.g., /k/ → c, k, qu.…”
Section: Modeling Written Picture Namingmentioning
confidence: 99%